Diminished performance on neuropsychological testing in late life depression is correlated with microstructural white matter abnormalities - Mettenburg, Joseph M (2012)
BACKGROUND: Traditional T2 weighted MR imaging results are non-specific for the extent of underlying white matter structural abnormalities present in late life depression (LLD). Diffusion tensor imaging provides a unique opportunity to investigate the extent and nature of structural injury, but has been limited by examining only a subset of regions of interest (ROI) and by confounds common to the study of an elderly population, including comorbid vascular pathology. Furthermore, comprehensive correlation of diffusion tensor imaging (DTI) measurements, including axial and radial diffusivity measurements, has not been demonstrated in the late life depression population. METHODS: 51 depressed and 16 non-depressed, age- and cerebrovascular risk factor- matched elderly subjects underwent traditional anatomic T1 and T2 weight imaging, as well as DTI. The DTI data were skeletonized using tract based spatial statistics (TBSS), and both regional and global analyses were performed. RESULTS: Widespread structural abnormalities within white matter were detected in the LLD group, accounting for age, gender and education and matched for cerebrovascular risk factors and global T2 white matter hyperintensities (T2WMH). Regional differences were most prominent in uncinate and cingulate white matter and were generally characterized by an increase in radial diffusivity. Age-related changes particularly in the cingulate bundle were more advanced in individuals with LLD relative to controls. Regression analysis demonstrated significant correlations of regional fractional anisotropy and radial diffusivity with five different neuropsychological factor scores. TBSS analysis demonstrated a greater extent of white matter abnormalities in LLD not responsive to treatment, as compared to controls. CONCLUSIONS: White matter integrity is compromised in late life depression, largely manifested by increased radial diffusivity in specific regions, suggesting underlying myelin injury. A possible mechanism for underlying myelin injury is chronic white matter ischemia related to intrinsic cerebrovascular disease. In some regions such as the cingulate bundle, the white matter injury related to late-life depression appears to be independent of and compounded by age-related changes. The correlations with neuropsychological testing indicate the essential effects of white matter injury on functional status. Lastly, response to treatment may depend on the extent of white matter injury, suggesting a need for intact functional networks.